Phytochemicals of Periploca aphylla Dcne. ameliorated streptozotocin-induced diabetes in rat - Rashid, Umbreen (Environ Health Prev Med, 2021)
BACKGROUND: Periploca aphylla is used by local population and indigenous medicine practitioners as stomachic, tonic, antitumor, antiulcer, and for treatment of inflammatory disorders. The aim of this study was to evaluate antidiabetic effect of the extract of P. aphylla and to investigate antioxidant and hypolipidemic activity in streptozotocin (STZ)-induced diabetic rats. METHODS: The present research was conducted to evaluate the antihyperglycemic potential of methanol extract of P. aphylla (PAM) and subfractions n-hexane (PAH), chloroform (PAC), ethyl acetate (PAE), n-butanol (PAB), and aqueous (PAA) in glucose-overloaded hyperglycemic Sprague-Dawley rats. Based on the efficacy, PAB (200 mg/kg and 400 mg/kg) was tested for its antidiabetic activity in STZ-induced diabetic rats. Diabetes was induced via intraperitoneal injection of STZ (55 mg/kg) in rat. Blood glucose values were taken weekly. HPLC-DAD analysis of PAB was carried out for the presence of various polyphenols. RESULTS: HPLC-DAD analysis of PAB recorded the presence of rutin, catechin, caffeic acid, and myricetin. Oral administration of PAB at doses of 200 and 400 mg/kg for 21 days significantly restored (P < 0.01) body weight (%) and relative liver and relative kidney weight of diabetic rats. Diabetic control rats showed significant elevation (P < 0.01) of AST, ALT, ALP, LDH, total cholesterol, triglycerides, LDL, creatinine, total bilirubin, and BUN while reduced (P < 0.01) level of glucose, total protein, albumin, insulin, and HDL in serum. Count of blood cells and hematological parameters were altered in diabetic rats. Further, glutathione peroxidase, catalase, superoxide dismutase, glutathione reductase, and total soluble protein concentration decreased while concentration of thiobarbituric acid reactive substances and percent DNA damages increased (P < 0.01) in liver and renal tissues of diabetic rats. Histopathological damage scores increased in liver and kidney tissues of diabetic rats. Intake of PAB (400 mg/kg) resulted in significant improvement (P < 0.01) of above parameters, and results were comparable to that of standard drug glibenclamide. CONCLUSION: The result suggests the antihyperglycemic, antioxidant, and anti-inflammatory activities of PAB treatment in STZ-compelled diabetic rat. PAB might be used as new therapeutic agent in diabetic patients to manage diabetes and decrease the complications.